From Firm-Level Imports to Aggregate Productivity : Evidence from Korean Manufacturing Firms Data - Ahn, JaeBin (IMF Working Papers; Working Paper ;, 2016)
Using the Korean manufacturing firm-level data, this paper confirms that three stylized facts on importing hold in Korea: the ratio of imported inputs in total inputs tends to be procyclical; the use of imported inputs increases productivity; and larger firms are more likely to use imported inputs. As a result, we find that firm-level import decisions explain a non-trivial fraction of aggregate productivity fluctuations in Korea over the period between 2006 and 2012. Main findings of this paper suggest a possible link between the recent global productivity slowdown and the global trade slowdown.